Location Size and Orientation Effect of Semi elliptical Surface Crack on the Fracture of a Type 3 Composite Pressure Vessel using J integral Method - Çetin, Muzaffer; Yaman, Kemal (Defence Science Journal, 2020)
In this study, structural design and analysis of a type-3 composite over wrapped pressure vessel used in a military satellite propulsion system is presented. The aim is to design a composite tank lighter than all metal fuel tanks having the same volume. Moreover, necessary design stages have been revealed for similar composite over wrapped pressure vessels. ANSYS® is used to perform the stress-strain analysis of both metal and composite parts, to determine the optimum winding angle, tank Autofrettage and fracture characteristic for the metal liner considering the crack morphology. Tsai-Hill, Tsai-Wu and Hashin theories have been implemented to investigate the various failure modes of the composite vessel. Location, size and orientation angle of semi-elliptical surface crack has a pronounced effect on fracture characteristic of the liner. In fracture investigation J-integral method is used. It is foreseen that even in the most critical crack, the crack will not propagate and there will be no burst in the tank for proposed loading conditions. Numerical results are good agreement with the experimental results.